„Ovidius” library through multicultural communication towards institution internationalization (Confluenţe Bibliologice, 2015)
„Ovidius” Library opens new ways and partnerships to promote multicultural communication in a multicultural world with great ethnic diversity. In this regard were inaugurated various activities, one of which reading Club for users „Café littéraire”. The purpose of the Club is to promote young writers and translators. The author describes the organization of literary-musical events devoted to „International Day of Francophonie” and „World Day of Poetry,” a roundtable „European Day of Languages” with discussions about the 24 European oﬃcial languages spoken, and other 45 local languages used in European forums. These events taught participants how to say greetings in 20 languages. Knowledge of European values occurs through the Project „I want to be European” launched in 2015.
Keywords: European integration; library users